2020
DOI: 10.1002/jat.4038
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between urinary β2‐microglobulin concentration and mortality in a cadmium‐polluted area in Japan: A 35‐year follow‐up study

Abstract: The relationship between urinary β 2-microglobulin (β 2-MG) and the risk of all-cause mortality and cause-specific mortality in a cadmium (Cd)-polluted area was investigated in 3139 inhabitants (1404 men and 1735 women) of the Kakehashi River basin in Japan at 35-year follow-up. The subjects had been participants in the 1981-1982 health impact survey that assessed Cd-induced renal dysfunction, as measured by the urinary β 2-MG concentration. Hazard ratios were calculated to assess the risk of all-cause and cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The results showed that the urinary Cd concentration was significantly associated with mortality from heart failure in women and from diseases of the digestive system in men, even after adjustment for other causes of death using the Fine and Gray competing risk regression model. We previously reported that the urinary β2-MG concentration was associated with a high risk of mortality from renal disease, but not from other causes, in both men and women of the present cohort, as revealed by a competing risk model [8]. The kidney is a target of external Cd, and renal tubular dysfunction is the most prevalent adverse health effect induced by Cd exposure.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The results showed that the urinary Cd concentration was significantly associated with mortality from heart failure in women and from diseases of the digestive system in men, even after adjustment for other causes of death using the Fine and Gray competing risk regression model. We previously reported that the urinary β2-MG concentration was associated with a high risk of mortality from renal disease, but not from other causes, in both men and women of the present cohort, as revealed by a competing risk model [8]. The kidney is a target of external Cd, and renal tubular dysfunction is the most prevalent adverse health effect induced by Cd exposure.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, no significant association was observed between Cd exposure and any cause-specific mortality in participants with severe renal tubular dysfunction. We previously reported that the urinary concentration of β2-MG, a marker of renal tubular dysfunction, was associated with all-cause mortality as well as renal disease-specific mortality in inhabitants of a Cd-polluted area [8]. Renal tubular dysfunction may directly increase the risk of death from renal disease regardless of Cd exposure, suggesting that Cd is not associated with death in participants with severe renal damage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A concentration of β2-MG exceeding 300 µg/g creatinine in the urine indicates defective tubular reabsorption [25]. Damage of this degree increases the risk of death due to kidney and urinary tract diseases [150]. Numerous studies have shown that the concentration of β2-MG in the urine rises with increasing exposure to Cd and an increasing concentration of this xenobiotic in the urine [9,37,40,45,145,151,152].…”
Section: Biomarkers Of Cd-induced Kidney Damagementioning
confidence: 99%